The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1140/epjc/s10052-018-6126-0
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quarkonium production through the top quark rare decays via the channels involving flavor changing neutral currents

Abstract: In the paper, we discuss the possibility of observation of heavy quarkoniums via the processes involving flavor changing neutral currents (FCNC). More explicitly, we systematically calculate the production of heavy charmonium and (cb)-quarkonium through the top quark semiexclusive rare FCNC decays in the framework of the nonrelativistic QCD (NRQCD) factorization theory. Our results show that the total decay widths t→η c = 1.20 GeV, where the uncertainties are from variation of quark masses and renormalization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…We found that our work gives better results in comparison with experimental data. In [20,21,28,29], the authors used the same method and the same potential when = 0. We noticed that our work is in better agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…We found that our work gives better results in comparison with experimental data. In [20,21,28,29], the authors used the same method and the same potential when = 0. We noticed that our work is in better agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 99%